Investigations of ancient terra-cotta sarcophagi, excavated in Enez (Ainos) Turkey, by Instrumental Neutron Activation Analysis - Mukhamedshina, Nuranya M.; Balcı, Kubilay; Mirsagatova, A. Adiba; Kurap, Gülnur; Basarans, Sait; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Croatian Chemical Soc, Marulicev Trg 19/Ii, 41001 Zagreb, Croatia, 2015)
Ten terra-cotta sarcophagi, together with a terra-cotta aryballos (perfume jar), excavated in Su Terazisi necropolis of Enez-Turkey (Ancient Ainos), were investigated by Instrumental Neutron Activation Analysis (INAA), to determine the concentration of thirty two chemical elements: Na, K, Ca, Fe, Sc, Cr, Mn, Co, Ni, Cu, Zn, As, Se, Br, Rb, Sr, Sb, Cs, Ba, La, Ce, Nd, Sm, Eu, Tb, Dy, Yb, Lu, Hf, Ta, Th and U. The dataset was submitted to multivariate statistical analysis. The classification was done by cluster analysis. The results demonstrated the occurrence of two different groups of terra-cotta samples. Group I contains nine sarcophagi and terra-cotta aryballos whereas group II contains only one sample (E09-ST5-M26). High correlations between La and Ce (r(2) = 0.92), and U and Th (r(2) = 0.91) indicated that local clay was used for manufacturing the terra-cotta sarcophagi and aryballos but probably the claybed used for E09-ST5-M26 was different from that of others.
Keywords: Ancient terra-cotta sarcophagi; Archaeometry; Instrumental neutron activation analysis